PENGGUNAAN MANAJEMEN KONFLIK DITINJAU DARI STATUS KEIKUTSERTAAN DALAM MENGIKUTI KEGIATAN PECINTA ALAM DI UNIVERSITAS GADJAH MADA YOGYAKARTA - Adi Mardianto; - Koentjoro; Esti Hayu Purnamaningsih (Faculty of Psychology, Universitas Gadjah Mada, 2000)
The aim of this study was to investigate differences using conflict management between students whose followed and not followed Pecinta Alam activities on to face interpersonal conflict in daily life. Subject of each group were 98 students. The study used measuring instruments in form of scale, namely conflict management scale that modified by Kurdek (1994) and Personality scale from Bortner. The parameters of the research were the state of following Pecinta Alam activity, sex and type of personality. By using 3 ways varians analysis, the result of the study were: 1. There was differences in the use of conflict management between the students whose followed and not followed Pecinta Alam activity, where the first one have the ability of the use of conflict management more constructive than the second one. 2. There was differences in the use of conflict management between men sudents and women students. 3. There was no difference in the use of conflict management between student with Personality type A and type B. Keywords: Conflict management, pecinta alam activity.